Faktor Faktor yang Mempengaruhi Opini Audit Going Concern Pada Perusahaan Manufaktur di Bursa Efek Indonesia - Syailendra Eka Saputra; Alfattory Rheza Syahrul; Gustia Harini (Universitas Dharma Andalas, 2022)
This study aims to determine the effect of a number of factors that influence the provision of going concern audit opinions on manufacturing companies on the Indonesia Stock Exchange. In this study, the factors that are thought to influence the provision of going concern audit opinions consist of audit tenure, opinion shopping, audit delay and financial distress. The data analysis method used is binary logistic regression. Based on the results of hypothesis testing, it was found that audit tenure and opinion shopping had no significant effect on going concern audit opinions on manufacturing companies on the Indonesia Stock Exchange, while audit delay and financial distress had a significant effect on going concern audit opinions on manufacturing companies on the Indonesia Stock Exchange. ABSTRAK Penelitian ini bertujuan mengetahui pengaruh sejumlah faktor yang mempengaruhi pemberian opini audit going concern pada perusahaan manufaktur di Bursa Efek Indonesia. Pada penelitian ini faktor yang diduga mepengaruhi pemberian opini audit going concern terdiri dari audit tenure, opinion shoping, audit delay dan financial distress. Metode analisis data yang digunakan adalah regresi binary logistic. Berdasarkan hasil pengujian hipotesis ditemukan audit tenure dan opinion shoping tidak berpengaruh signifikan terhadap opini audit going concern pada perusahaan manufaktur di Bursa Efek Indonesia, sedangkan audit delay dan financial distress berpengaruh signifikan terhadap opini audit going concern pada perusahaan manufaktur di Bursa Efek Indonesia.